2019
DOI: 10.14393/bj-v35n5a2019-42268
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds in wines produced in a new area for vitiviniculture in Brazil

Abstract: Wines are known for its high content of bioactive compounds that can be influenced by the region and climate where the grapes are produced. New regions of production are normally developed using techniques and standards for other traditional regions, but is important to characterize the wine profile, which is different according to the terroir, and can be important for future geographic indications. The aim of this study was to evaluate color, antioxidant activity, anthocyanin content and phenolic compounds pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…There are even mathematical models to predict the production of these compounds during the winemaking process. In this work, we found that optimized blueberry wine had phenolic compounds, as reported by other authors for wines from blueberry; thus, we can conclude that the consumption of optimized blueberry wine could have beneficial effects on health, just like other types of wines that have been previously studied (Castaldo et al, 2019;Miller & Block, 2020;Olas, 2018;Ortiz et al, 2013;Vilas-Boas et al, 2019).…”
Section: Antioxidant Activitysupporting
confidence: 85%
See 2 more Smart Citations
“…There are even mathematical models to predict the production of these compounds during the winemaking process. In this work, we found that optimized blueberry wine had phenolic compounds, as reported by other authors for wines from blueberry; thus, we can conclude that the consumption of optimized blueberry wine could have beneficial effects on health, just like other types of wines that have been previously studied (Castaldo et al, 2019;Miller & Block, 2020;Olas, 2018;Ortiz et al, 2013;Vilas-Boas et al, 2019).…”
Section: Antioxidant Activitysupporting
confidence: 85%
“…Regarding the phenolic compounds content, differences in the anthocyanin content could be due to blueberry cultivars characteristics, the winemaking process and climatic growing conditions. It has been reported that wines made from grapes in higher altitudes have higher anthocyanin content (Liu, Zhang, Shi, Duan, & He, 2019;Vilas-Boas et al, 2019), so that the wine obtained from blueberries at sea level may be different from those reported in the literature.…”
Section: Total Anthocyanin Contentmentioning
confidence: 79%
See 1 more Smart Citation